2023
DOI: 10.1007/s11625-023-01342-z
|View full text |Cite|
|
Sign up to set email alerts
|

Unlocking and accelerating transformations to the SDGs: a review of existing knowledge

Abstract: As we cross the 2030 deadline to achieve the Sustainable Development Goals (SDGs), there is a growing sense of urgency around the need to accelerate the necessary transformations. These encompass a broad range of systems and require fundamental changes in system goals and design. In this paper, we undertake a narrative review of the literature relating to the acceleration of transformations and offer a framework for unlocking and accelerating transformations to the SDGs. While there is no blueprint for acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 161 publications
0
4
0
Order By: Relevance
“…Extant research across various disciplines provides numerous empirical models, confirming the criticality of sustainable development for our society (Allen and Malekpour, 2023; Clark and Harley, 2020). Although previous studies lack consensus about the optimal scenario for facilitating sustainable development, they indicate effective alternative pathways to a more sustainable future.…”
Section: Introduction To the Special Issuementioning
confidence: 87%
“…Extant research across various disciplines provides numerous empirical models, confirming the criticality of sustainable development for our society (Allen and Malekpour, 2023; Clark and Harley, 2020). Although previous studies lack consensus about the optimal scenario for facilitating sustainable development, they indicate effective alternative pathways to a more sustainable future.…”
Section: Introduction To the Special Issuementioning
confidence: 87%
“…If we don't quadruple our current progress rate for SDG6, billions will still lack access to clean water and sanitation by 2030 [13]. Yet, there is little evidence that any acceleration in effort is occurring or emerging [14]. Why has this occurred?…”
Section: In Perspective: Climate Change Sdg 6 and Institutional Failuresmentioning
confidence: 99%
“…The global ecological balance between environmental preservation and economic growth has increasingly become a paramount concern for nations worldwide. The 2023 Global Sustainable Development Report (GSDR), published by the United Nations, emphasizes the imperative of aligning future development with sustainable practices, integrating environmental preservation with economic progress [1]. Numerous studies have demonstrated the escalating harm inflicted on ecosystems by human activities.…”
Section: Introductionmentioning
confidence: 99%